Wise Computing: Toward Endowing System Development with Proactive Wisdom. - Harel, David; Katz, Guy; Marelly, Rami; Marron, Assaf (Computer (00189162), 2018)
A broad, long-term research project is described, which will lead to the computer becoming an equal member of the system-development team, continuously making proactive contributions, akin to those expected from an experienced and knowledgeable customer or user, a conscientious QA engineer, a strict regulatory auditor, an engineering -team leader, or the organization’s CTO. The web extra at https://youtu.be/mmrv8ZACbpU describes the authors’ novel “wise computing” approach and demonstrates one possible application. The second web extra at https://youtu.be/DtpvMxMwYPM extends the discussion of the authors’ novel “wise computing” approach and presents a case study.